(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Gurcharan Das book The Difficulty of Being Good: On the Subtle Art of Dharma is a work in the ’spiritual but not religious’. This book is an extended essay on dharma (a term that can be translated as ’right action’ or ’duty’), which Gurcharan Das defines as the virtue that allows us to be good in spirit, even when it is difficult to be good in practice. He points out how in many ways, the notion of dharma has been undermined by modernity, which has made us believe that happiness and goodness are two separate things.